Determinan Simpanan Deposito Mudharabah Bank Umum Syariah di Indonesia - Ulfah Indriyani; Syihabudin Syihabudin; Tenny Badina; Rita Rosiana (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2021)
This study aims to examine the effect of Profit Sharing Deposit, Interest Rate and Financing to Deposit Ratio on the amount of Mudharabah Deposit in Islamic Commercial Banks in Indonesia for the 2013-2017 Period. The population used in this study are Sharia Commercial Banks (BUS) registered with the Financial Services Authority (OJK) for the 2013-2017 period. The sample of this research is 8 Islamic Commercial Banks (BUS) from a total population of 13 Islamic Commercial Banks (BUS). Sampling using purposive sampling. The analysis method used in this research is the classical assumption test, multiple regression analysis, simultaneous test (F test), partial test (t test), and determination coefficient test. The results showed that: (1) Profit Sharing Deposit has a positive and significant effect on Mudharabah Deposits, (2) Interest Rates have no effect on Mudharabah Deposits, (3) Financing to Deposit Ratio (FDR) has no effect on Mudharabah Deposits.